ANALISIS PERBANDINGAN DONGENG ISSUNBOUSHI DAN SI KELINGKING - Yoga Arisaputra I Made; Ni Luh Gede Meilantari (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2025)
This study discusses cultural elements in the Indonesian fairy tales of Si Kelingking and Issunboushi from Japan, focusing on the social organization system, livelihood, arts, religion, language, and technology system. A descriptive qualitative approach is used to analyze the similarities and differences between the two fairy tales. The results show that Si Kelingking emphasizes family-based and kingdom-based social organizations, and depicts a diversity of livelihoods through farming and hunting. In contrast, Issunboushi focuses more on agriculture as a source of livelihood. In terms of art, Si Kelingking displays a wedding feast that reflects the collective values ​​of society, while Issunboushi displays kenjutsu (martial arts) and waka (classical poetry), which emphasize philosophical values. In terms of religion, Si Kelingking reflects traditional beliefs based on myths and nature, while Issunboushi is influenced by Buddhist teachings with an emphasis on morality and spirituality. Another difference is seen in the use of language, where Si Kelingking uses Indonesian with Malay influences, while Issunboushi uses everyday Japanese. In terms of technology, Si Kelingking features simple elements such as "kerusung" clothing, village settlements, and horses, while Issunboushi highlights the more complex sokutai, goten, and ox carts. This study concludes that both fairy tales reflect unique local cultural values, while also showing how universal cultural elements can be adapted to the social, geographical, and historical contexts of each society. Keywords: Analysis, comparison, fairy tales, Si Kelingking, Issunboushi.